Efektivitas ekstrak etanol daun mimba (azadirachta indica) terhadap kematian larva nyamuk aedes aegypti - Lusi Martha Indrayani; I Made Sudarmaja (Universitas Udayana, 2018)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by dengue virus. The virus is also transmitted through the bites of infected mosquito. The Aedes aegypti mosquito is the primary vector that spreads this disease. In Indonesia, the prevention of this disease is still not optimal. It can be seen through the number of cases increasing every year. The use of plant-based insecticides integrated with environmental management is the way to prevent or control the transmission of Aedes aegypti . One of plant-based insecticides is neem (Azadirachta indica) leaf. The aim of this research was to know the effectiveness of neem (Azadirachta indica) leaf extract on the mortality of Aedes aegypti larvae.This research was experimental research used post -test and control group design. The sample was 168 of third instar larvae of Aedes aegypti . This research used six kinds of treatment toward neem (Azadirachta indica) leaf extract. They are 1%, 1.5 %, 2 %, 2.5 %, 3% and 3.5 %. Then, there is 3 times of repetition. Each treatment consist of 8 larvae. The data were analyzed by using Kruskal - Wallis test and Mann Whitney. The result of Kruskal - Wallis test showed p=0.004 (p<0.05) that meant statistically difference of mortality rates of Aedes aegypti larvae among the samples. The result of Mann Whitney showed the significant differences between the concentration of 1%, 1.5 %, 2 %, 2.5 %, 3%, 3.5 % with the control.The highest mean of concentration is on 2.5%, 3%, 3.5% that was 8 (100%) during 24-hour observation. Then, it can be concluded that neem (Azadirachta indica) leaf extract had potential as biolarvacide on Aedes aegypti larvae. Finally, further research is needed with the larger sample and greater variety of concentreation. Keywords: Neem leaf extract, larvacides, Aedes aegypti